Risk and ambiguity preferences and the adoption of new agricultural technologies: Evidence from field experiments in rural India - Ward, Patrick S.; Singh, Vartika (International Food Policy Research Institute, 2014)
Advances in agricultural development have largely been a direct result of increased usage of new technologies. Among other important factors, farmers’ perceptions of risks associated with the new technology as well as their ability or willingness to take risks greatly influences their adoption decisions. In this paper we conduct a series of field experiments in rural India in order to measure preferences related to risk, potential loss, and ambiguity. Disaggregating by gender, we find that on average women are significantly more risk averse and loss averse than men, though the higher average risk aversion arises due to a greater share of women who are extremely risk averse.